(untitled) (Journal of Atomic and Molecular Sciences, 2014)
In this study we determined the effect of geometry of ring electrode on the operation of a new ion trap with cylindrical ring electrode and hyperbolical end cap electrode. This model indicated how adjusting the geometric cell parameters could reduce the impact of presence of higher order fields. Our work also illustrated the possibility of improving other desired properties of a trap. For example we found how these adjustments could minimize the non-linear effects. We also noticed the possibility of increasing the time of ion storage in a trap by the effect of one field in a hybrid ion trap. In this study we have obtained all of the equations of motion in a trap analytically.